A Novel Imprinted Gene (Sp-Pol) With Sex-Specific SNP Locus and Sex-Biased Expression Pattern Provides Insights Into the Gonad Development of Mud Crab (Scylla paramamosain) - Farhadi, Ardavan; Shi, Xi; Zhang, Yin; Zhang, Yueling; Li, Shengkang; Zheng, Huaiping; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Marine Science, 2021)
Identification and exploring the role of novel sex-related genes is a crucial step for understanding the regulation mechanism of sexual development. In the present study, we identified a novel sex-related gene (designated as Sp-Pol) upstream of a sex-specific single nucleotide polymorphism (SNP). SNP1888 together with Sp-Pol were mapped on LG32 (which is a sex-related linkage group) of a high-density genetic map. The full-length cDNA of Sp-Pol consists of 1703 bp with an open reading frame (ORF) encoding 204 amino acids, a 344 bp 5′-UTR and a 744 bp 3′-UTR. Phylogenetic analysis showed that Sp-Pol may need to be classified as a new gene family due to the very low sequence identity with other known genes (less than 25% identity). The sex-biased expression pattern of Sp-Pol starts from crablet stage V (C5) with approximately 3- to 4-fold higher in males than in females. Sp-Pol was expressed at a higher level in gonads compared to other tissues, with the highest expression level in the testis. In testis, a downward trend was observed in the expression level of Sp-Pol from the testis stage I (T1) to testis stage III (T3). After unilateral eyestalk ablation, the expression level of Sp-Pol significantly increased in testis and hepatopancreas in males, while it was downregulated in the hepatopancreas of females. Fluorescence in situ hybridization (FISH) assay revealed that Sp-Pol transcripts were strongly localized in the epithelia of seminiferous tubules of the testis, and in the ovary, it was detected in the oogonium cells. These findings showed that Sp-Pol may play crucial roles in the gonad development of S. paramamosain.